The Effect of Picture Storybook Media on the Reading Ability of Class II Students - Sa’idatul Hasanah; Sahkholid Nasution (Dinasti Publisher, 2024)
This research aims to determine the effect of using picture storybook media on the reading ability of class II students at SDS Al-Washliyah 11 Medan Amplas District. This research uses a quantitative approach with pre-experimental methods, using a one-group pretest-posttest design. The research sample consisted of 32 students, with a total sampling technique. Research instruments include tests, observations and interviews. Data were analyzed using SPSS version 25, with normality, homogeneity and paired sample t-tests. The research results showed that there was a significant increase in students' reading ability after using picture storybook media, with an average pretest score of 51.09 and posttest of 80.00. The significance of the t test shows a value of 0.00 < 0.05, which means there is a significant difference between the pretest and posttest results. Thus, the use of picture storybook media has a positive effect on students' reading abilities.